Perkembangan Moral Dan Keimanan Anak Usia Dini Melalui Metode Bercerita Di TPA Al-Husna Kota Bandung - Fera Juniyanti; Taufik Maulana; Dita Handayani (Universitas Muhammadiyah Bandung, 2024)
In the process of instilling moral values and faith in early childhood, we must look at the stage of child development. Instilling morals and faith in children can be realized by participating in school activities, children will get real experiences provided by the teacher. one of the methods used by teachers to instill morals and faith in children through storytelling activities. The need to instill morals and faith in the storytelling method is expected to make the values taught can be lived and interpreted by children without coercion. The research method used is qualitative method with data collection techniques. The findings of this study are that storytelling method activities can affect children's morals and faith when these activities are carried out with the right delivery, the right story selection, and by providing exemplary examples. The storytelling method can influence children's moral behavior and faith, but this activity is not enough. Therefore, teachers and parents must establish good cooperation. The purpose of this study is to determine the effectiveness of the storytelling method in instilling morals and faith in children of TPA Al-Husna, and to find out the supporting and inhibiting factors when the storytelling method is carried out at school. Efforts made by teachers to instill morals and faith in children so that children can understand and practice them in their daily lives. So that the development of morals and faith in early childhood develops well.